The Impact of Osteoporosis on Adverse Outcomes After Short Fusion for Degenerative Lumbar Disease. Issue 12 (15th June 2022) - Wolfert, Adam J.; Rompala, Alexander; Beyer, George A.; Shah, Neil V.; Ikwuazom, Chibuokem P.; Kim, David; Shah, Sharan T.; Passias, Peter G.; Lafage, Virginie; Schwab, Frank J.; Paulino, Carl B.; Diebo, Bassel G.
Abstract : Introduction: Osteoporosis affects nearly 200 million individuals worldwide. There are little available data regarding outcomes in patients with osteoporosis who undergo short-segment lumbar fusion for degenerative disk disease (DDD). We sought to identify a relationship between osteoporosis and risk of adverse outcomes in patients with DDD undergoing short-segment lumbar fusion. Methods: Using the New York State Statewide Planning and Research Cooperative System, all patients with DDD who underwent 2- to 3-level lumbar fusion from 2009 through 2011 were identified. Patients with bone mineralization disorders and other systemic and endocrine disorders and surgical indications of trauma, systemic disease(s), and infection were excluded. Patients were stratified by the presence or absence of osteoporosis and compared for demographics, hospital-related parameters, and 2-year complications and revision surgeries. Multivariate binary logistic regression models were used to identify notable predictors of complications. Results: A total of 29, 028 patients (osteoporosis = 1, 353 [4.7%], nonosteoporosis = 27, 675 [95.3%]) were included. Patients with osteoporosis were older (66.9 vs 52.6 years), more often female (85.1% vs 48.4%), and White (82.8% vs 73.5%) (all P < 0.001). The Charlson/Deyo comorbidity index did not significantly differ between groups. Hospital lengths of stay and total charges were higher for patients with osteoporosis (4.9 vs 4.1 days; 74, 484 vs 73, 724; both P < 0.001). Medical complication rates were higher in patients with osteoporosis, including acute renal failure and deep-vein thrombosis (both P < 0.01). This cohort also had higher rates of implant-related (3.4% vs 1.9%) and wound (9.8% vs 5.9%) complications (both P < 0.01). Preoperative osteoporosis was strongly associated with 2-year medical and surgical complications (odds ratios, 1.6 and 1.7) as well as greater odds of revision surgeries (odds ratio, 1.3) (all P < 0.001). Conclusion: Patients with osteoporosis undergoing 2- to 3-level lumbar fusion for DDD were at higher risk of 2-year medical and surgical complications, especially implant-related and wound complications. These findings highlight the importance of rigorous preoperative metabolic workup and patients' optimization before spinal surgery.